VD_FINDINFO HC / 2022 / 825 vom 31. August 2022 - VD Tribunal cantonal (2022)
OBLIGATION DE CHIFFRER LES CONCLUSIONS, FORMALISME EXCESSIF, APPEL EN CAUSE | 319 let. b ch. 1 CPC (CH), 81 al. 1 CPC (CH), 82 CPC (CH)